Geometry matters: inverse cytotoxic relationship for cis/trans-Ru(ii) polypyridyl complexes from cis/trans-[PtCl2(NH3)2]. Issue 66 (29th June 2016) - Wachter, Erin; Zamora, Ana; Heidary, David K.; Ruiz, José; Glazer, Edith C.
Abstract : Two thermally activated ruthenium(ii ) polypyridyl complexes, cis -Ru(bpy)2 Cl2 and trans -Ru(qpy)Cl2 were investigated to determine the impact of the geometric arrangement of the exchangable ligands on the potential of the compounds to act as chemotherapeutics. Abstract : Two thermally activated ruthenium(ii ) polypyridyl complexes, cis -Ru(bpy)2 Cl2 and trans -Ru(qpy)Cl2 were investigated to determine the impact of the geometric arrangement of the exchangable ligands on the potential of the compounds to act as chemotherapeutics. In contrast to the geometry requirements for cisplatin, trans -Ru(qpy)Cl2 was 7.1–9.5× more cytotoxic than cis -Ru(bpy)2 Cl2 . This discovery could open up a new area of metal-based chemotherapeutic research.